2012
DOI: 10.1007/s15010-012-0336-4
|View full text |Cite
|
Sign up to set email alerts
|

Extrapulmonary mycobacterial infections in a cohort of HIV-positive patients: ultrasound experience from Vicenza, Italy

Abstract: As disseminated mycobacterial infections in HIV-positive patients can be treated effectively if diagnosed early, and typical sonographic findings are seen in the majority of these patients, we suggest that POC ultrasound should be integrated in diagnostic and screening algorithms for EPTB in developed countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…The pattern of multiple hypo-echoic lesions in the spleen, and less frequently, in the liver, has been described as highly suggestive for disseminated TB and has been included into point-of-care US protocols for extra-pulmonary TB. 26 Miliary TB lesions are most frequently seen in immune-compromised HIV patients 27 but have also been reported in children without HIV coinfection. 28 Infection with Bartonella, for example, HIV-associated bacillary angiomatosis or cat-scratch-disease may cause peliosis 29 which is another differential diagnosis of hypo-echoic focal lesions, but peliosis is rare and associated with a positive serology for Bartonella.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of multiple hypo-echoic lesions in the spleen, and less frequently, in the liver, has been described as highly suggestive for disseminated TB and has been included into point-of-care US protocols for extra-pulmonary TB. 26 Miliary TB lesions are most frequently seen in immune-compromised HIV patients 27 but have also been reported in children without HIV coinfection. 28 Infection with Bartonella, for example, HIV-associated bacillary angiomatosis or cat-scratch-disease may cause peliosis 29 which is another differential diagnosis of hypo-echoic focal lesions, but peliosis is rare and associated with a positive serology for Bartonella.…”
Section: Discussionmentioning
confidence: 99%
“…During the screening process, we found 22 articles that discussed the presence of splenic microabscesses in patients with HIV and TB co-infection. [12,21,24,27,28,30,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] These articles were excluded because Murray et al [39] (1995) n=7 (100%), 95% CI 59.0 -100…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that in individuals with a clinically high risk of tuberculosis, these findings are sufficiently specific to initiate anti-TB treatment [3] . Nevertheless, in settings outside Sub-Saharan Africa and other settings with limited resources, it seems prudent to perform US-guided biopsy and aspiration of the lesions for bacteriological confirmation of the diagnosis [12] . In our series, biopsy/aspiration was the diagnostic procedure in 14 patients (38%).…”
Section: Discussionmentioning
confidence: 99%